2020
DOI: 10.1093/cid/ciaa1255
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Controlled Trial of Intravenous N-Acetylcysteine in the Management of Anti-tuberculosis Drug–Induced Liver Injury

Abstract: Background Liver injury is a common complication of first-line anti-tuberculosis therapy. N-acetylcysteine (NAC) is widely used in patients with paracetamol toxicity with limited evidence of benefit in liver injury due to other causes. Methods We conducted a randomized, double-blind, placebo-controlled trial to assess whether intravenous NAC hastens liver recovery in hospitalized adult patients with anti-tuberculosis drug ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 24 publications
1
31
0
1
Order By: Relevance
“…There were several reports of the use of NAC to treat DILI published over the last year [186,187]. Notably, we found a randomized controlled trial that evaluated the use of NAC for anti-TB-DILI [186]. Its results showed that although NAC did not shorten the time to ALT < 100 U/L in participants with anti-TB-DILI, it did significantly reduce the length of a hospital stay from 18 days to 9 days compared with placebo.…”
Section: Updates In Treatment and Preventionmentioning
confidence: 85%
See 1 more Smart Citation
“…There were several reports of the use of NAC to treat DILI published over the last year [186,187]. Notably, we found a randomized controlled trial that evaluated the use of NAC for anti-TB-DILI [186]. Its results showed that although NAC did not shorten the time to ALT < 100 U/L in participants with anti-TB-DILI, it did significantly reduce the length of a hospital stay from 18 days to 9 days compared with placebo.…”
Section: Updates In Treatment and Preventionmentioning
confidence: 85%
“…Other than treatment with intravenous N-acetylcysteine (NAC), there have been few other options for improving transplant-free survival in non-acetaminophen acute liver failure. There were several reports of the use of NAC to treat DILI published over the last year [186,187]. Notably, we found a randomized controlled trial that evaluated the use of NAC for anti-TB-DILI [186].…”
Section: Updates In Treatment and Preventionmentioning
confidence: 91%
“…Moosa MS et al conducted a randomized, double-blind, placebo-controlled trial to assess whether intravenous NAC hastens liver recovery in hospitalized adult patients with anti-tuberculosis (Anti-TB) DILI. The results revealed that NAC did not shorten time to ALT<100 U/L in participants with Anti-TB DILI, but significantly reduced length of hospital stay ( Moosa et al, 2020 ). In another study NAC together with prednisolone when used in cases of severe idiosyncratic DILI due to fupirtine (central acting non-opiod analgesic) showed a significant improvement in ALT, AST and INR within 2 weeks compared to those who were not treated with NAC ( Borlak et al, 2018 ).…”
Section: Pharmacotherapy Strategiesmentioning
confidence: 98%
“…Tuberculosis also arises in other organs, including bone and spine, then evolving into one of the most typical forms of extrapulmonary tuberculosis ( Pandey et al, 2009 ; Magnussen et al, 2013 ; Pigrau-Serrallach and Rodríguez-Pardo, 2013 ; Rodriguez-Takeuchi et al, 2019 ). Recently, the surgical intervention accompanied by indispensable anti-tubercular drug therapy is the primary routine treatment ( Mukewar et al, 2012 ; Shrivastava et al, 2019 ; Moosa et al, 2020 ; Phillips et al, 2020 ). Although rifampicin (RIF) and isoniazid have been widely chosen as clinical anti-tubercular drugs due to their excellent effectiveness and reasonable price ( Hakkimane et al, 2018 ; Campbell et al, 2020 ; Sterling et al, 2020 ; Villa et al, 2020 ; Kabir et al, 2021 ), their short plasma life and relatively low concentration in tuberculosis granulomas and the inescapable side effects of chemotherapeutic drugs have drawn growing attention from interdisciplinary and clinical medicine research circles ( Du Toit et al, 2006 ; Dartois, 2014 ; Liao et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%